ANTINEPHROLITHIATIC ACTIVITY OF PERSEA AMERICANA (AVOCADO) AND VIBURNUM OPULUS (GUELDER ROSE) AGAINST ETHYLENE GLYCOL-INDUCED NEPHROLITHIASIS IN RATS - Erdem, Galip; Kesik, Vural; Honca, Tevfik; Ozcan, Ayhan; Uguz, Sami; Akgul, Emin Ozgur; Aykutlug, Omer; Alp, Bilal Firat; Korkmazer, Nadir; Saldir, Mehmet; Bayrak, Ziya (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Nephrolithiasis is a severe health problem causing morbidity. Chemolisis, extracorporeal shock wave lithotripsy (SWL), percutaneous nephrolithotomy (PNL), retrograde ureterorenoscopy (URS), and open and laparoscopic surgery are used for treatment with various success rates. Medical treatments with fewer complications were investigated thoroughly. Materials and Methods: In this study, we evaluated the effects of Persea americana (avocado) leaves and Viburnum opulus (guelder rose) fruits on nephrolithiasis in an animal model and used 42 rats. The groups received both low and high doses of Persea americana leaves and Viburnum opulus fruit ethanol extracts orally for 28 days. These two plants have been used for years in Turkey for their nephrolithiatic effect. Results: Avocado and guelder rose increased the urine volume and urine citrate levels, decreased urine cystine and oxalate levels, and lowered the crystal deposits in kidney tissue. Avocado and guelder rose also prevented oxidant damage and crystal formation in kidney tissue samples. Conclusion: The two plants that have been used for years for nephrolithiasis treatment in Turkey can safely be used for kidney stones.